Subdividing the Holocene Series/Epoch: formalization of stages/ages and subseries/subepochs, and designation of GSSPs and auxiliary stratotypes. (23rd May 2019) - WALKER, MIKE; Head, Martin J.; Lowe, John; Berkelhammer, Max; BjÖrck, Svante; Cheng, Hai; Cwynar, Les C.; Fisher, David; Gkinis, Vasileios; Long, Antony; Newnham, Rewi; Rasmussen, Sune Olander; et al.
ABSTRACT: The Holocene, which currently spans ~11 700 years, is the shortest series/epoch within the geological time scale (GTS), yet it contains a rich archive of evidence in stratigraphical contexts that are frequently continuous and often preserved at high levels of resolution. On 14 June 2018, the Executive Committee of the International Union of Geological Sciences formally ratified a proposal to subdivide the Holocene into three stages/ages, along with their equivalent subseries/subepochs, each anchored by a Global boundary Stratotype Section and Point (GSSP). The new stages are the Greenlandian (Lower/Early Holocene Subseries/Subepoch) with its GSSP in the Greenland NGRIP2 ice core and dated at 11 700 a b2k (before 2000 CE); the Northgrippian (Middle Holocene Subseries/Subepoch) with its GSSP in the Greenland NGRIP1 ice core and dated at 8236 a b2k; and the Meghalayan (Upper/Late Holocene Subseries/Subepoch) with its GSSP in a speleothem from Mawmluh Cave, north‐eastern India, with a date of 4250 a b2k. We explain the nomenclature of the new divisions, describe the procedures involved in the ratification process, designate auxiliary stratotypes to support the GSSPs and consider the implications of the subdivision for defining the Anthropocene as a new unit within the GTS.